Hereditary - Aster, Ari; Wolff, Alex, 1997-; Byrne, Gabriel, 1950-; Collette, Toni (Santa Monica, California : Lionsgate, 2018)
When the matriarch of a family dies, terrifying things start happening to the members of the family.
Originally released as a motion picture in 2018.
Dolby digital 5.1, wide screen 1.85:1.
Alex Wolff, Gabriel Byrne, Toni Collette, Milly Shapiro, Ann Dowd.
MPAA rating: R.
In English with optional Spanish subtitles.
Closed-captioned.
Keywords: Families -- Drama; Death -- Drama; Fiction films; Video recordings for the hearing impaired; Feature films; Horror films